Zapisać w postaci sumy algebraicznej:
a) (2a+b)·c- (2ac-bc+1)
b)5(x-z)+2(z-x)
c)2x²(x-5)-3x(x²-3x+5)
d)6(a²+b+1/3)- 6 (a²- ½) -3 (b+1/3)



Odpowiedź :

a)

(2a + b) ·c - (2ac - bc + 1) = 2ac + bc - 2ac + bc - 1= 2bc - 1


b)

5(x - z) + 2(z - x) = 5x - 5z + 2z - 2x = 3x - 3z


c)

2x²(x - 5) - 3x(x² - 3x + 5) = 2x³ - 10x² - 3x³ + 9x² - 15x = -x³ - x² - 15x


d)

6(a² + b + 1/3) - 6 (a² - ½)  - 3 (b + 1/3) = 6a² + 6b + 2 - 6a² + 3 - 3b - 1 = 3b + 4

a)

2ac+bc-2ac+bc-1=2bc-1

b)

5x-5z+2z-2x=3x-3z

c)

2x³-10x²-3x³+9x²-15x=-x³-x²-15x

d)

6a²+6b+2-6a²+3-3b-1=3b+4